Is there a change in the appropriateness of admission after patients were admitted? Evidence from four county hospitals in rural China - Chang, Jingjing; Gao, Hongxia; Su, Dai; Li, Haomiao; Chen, Yingchun (Frontiers in Public Health, 2023)
Objective: This study aims to investigate the changes in the admission appropriateness after patients were admitted and provide a reference for physicians to make admission decisions and for the supervision of medical service behaviour by the medical insurance regulatory department. Methods: Medical records of 4,343 inpatients were obtained based on the largest and most capable public comprehensive hospital in four counties in central and western China for this retrospective study. Binary logistic regression model was employed to examine the determinants of changes in admission appropriateness. Results: Nearly two-in-thirds (65.39%) of the 3,401 inappropriate admissions changed to appropriate at discharge. Age, type of medical insurance, medical service type, status of the patient upon admission and disease category were found to be associated with the changes in the appropriateness of admission. Older patients (OR=3.658, 95% CI [2.462-5.435]; P <0.001) were more likely to go from "inappropriate" to "appropriate" than the younger counterparts. Compared with circulatory diseases, the case be evaluated as "appropriate" at discharge was more frequent in the urinary diseases (OR=1.709, 95% CI [1.019-2.865]; P = 0.042) and genital diseases (OR=2.998, 95% CI [1.737-5.174]; P<0.001), whereas the opposite finding was observed for patients with respiratory diseases (OR=0.347, 95% CI [0.268-0.451]; P <0.001) and skeletal and muscular diseases (OR=0.556, 95% CI [0.355-0.873]; P=0.011). Conclusions: Many disease characteristics gradually emerged after the patient was admitted, thus the appropriateness of admission changed. Physicians and regulators need to take a dynamic view of disease progression and inappropriate admission rates.Aside from referring the appropriateness evaluation protocol (AEP), they both should pay attention to individual and disease characteristics to make a comprehensive judgment, and strict control and attention should be paid to the admission of respiratory, skeletal and muscular diseases.